Standard and immunoproteasomes show similar peptide degradation specificities. Issue 12 (6th December 2014) - Zanker, Damien; Chen, Weisan
Abstract : Vertebrates have evolved to express major histocompatibility complexes (MHCs) that present peptides of the intra‐cellular proteome for immunosurveillance against viruses and tumor. The MHC class I (MHC‐I) processing and presentation pathway allows for scrutiny of all cellular proteins and peptides by CD8 + cytotoxic T cells. The proteasome is part of the specialised machinery that degrades proteins down to peptides with the correct sequence for MHC‐I binding. However, much conjecture lies as to how the various proteasome isoforms and their active subunits create antigenic peptides, and if the specialised immunoproteasome solely performs this job. In this issue of the European Journal of Immunology, Mishto et al. [ Eur. J. Immunol . 2014. 44: 3508‐3521] address this question through systematic biochemical peptide degradation studies and provide new insights into the functions of proteasome β‐subunits.